The impact of age on second language acquisition: a critical review - Dey, Manna; Amelia, Rizky; Setiawan, Ananda (Institute of Advanced Engineering and Science, 2024)
Age plays a significant role in second language acquisition (SLA). Research indicates that the ability to learn a second language declines with age. This study reviewed relevant studies on the impact of age on SLA in order to attain the best results as language learning methods should be tailored to the learner's age and specific needs. The results showed that younger learners are more proficient in acquiring a second language due to their brain's plasticity, which enables them to learn new information quickly. They can easily acquire the language’s pronunciation, grammar, and vocabulary through exposure and immersion. As learners age, their ability to learn a second language decreases. After adolescence, the brain becomes less plastic, and the acquisition of a second language becomes more challenging. Research also shows that language also has a positive impact on a country’s economic development, as well as improving the international relations of local entrepreneurs. However, adult learners can still learn a second language, but it may take more time and effort. Moreover, the motivation and learning strategies of language learners also play an essential role in SLA. Young learners may not have a strong motivation to learn a second language, while adult learners may have a higher motivation due to professional or personal reasons. Age is a crucial factor in SLA, but it is not the only determining factor. The learner’s motivation, learning strategies, and exposure to the second language also play a significant role in the acquisition of a second language.